Conflict-induced displacement as a catalyst for agricultural innovation: Findings from South Sudan - Leonardo, Elias; Dorward, Peter T.; Garforth, Chris J.; Sutcliffe, Chloe; Van Hulst, Freddy (Elsevier, 2019)
This article explores how conflict-induced displacement influences agricultural innovation processes and systems, and its implications after the return home or permanent resettlement of smallholder farmers. Results show that high rates of agricultural innovation occurred during displacement in the Sudanese Civil War (1983-2005), many of which were maintained afterwards. Respondents cited the need for adaptation to new social and physical circumstances, changed gender roles, and enhanced inter-household communication as contributing to increased opportunities for knowledge exchange, trade, and importantly, the development of new networks, modes of organisation and social norms. Furthermore, returnees to South Sudan have embodied these changes together with new values, habits and expectations. New linkages continued across borders between returnees and non-returnees, facilitating knowledge exchange and access to resources, markets and sources of ideas. A high degree of autonomous innovation capacity was also evident. Further research is required on the dynamics and processes associated with innovation in conflict-induced displacement. It is important for policy makers to encourage approaches that seek to actively tap into and build on the institutional, human and social capital built during displacement.
Keywords: Agricultural Innovation; Institutions; Extension; Post-conflict; Migration; Conflict